Collaborating with qualitative researchers to co‐design social‐ecological studies. (31st March 2022) - Keith, Ryan J.; Given, Lisa M.; Martin, John M.; Hochuli, Dieter F.
Abstract: In recent years, ecologists have embraced the human dimensions of their discipline and expanded their remit to explore issues traditionally addressed by the social sciences and environmental humanities. This expansion offers opportunities to engage with diverse methodologies, some of which challenge the orthodoxies of conservation research; however, ecologists do not have the expertise to use social science methodologies in their work. In this Toolkit, we outline ways to improve social‐ecological research and outcomes through partnerships with qualitative researchers. Ecologists – who lack the epistemological and methodological preparation needed for productive qualitative or mixed methods study design – have often used quantitative methods to investigate social‐ecological systems. Though this has enhanced our ecological knowledge and led to the development of evidence‐based conservation practices, the biodiversity crisis continues to worsen as a result of human behaviours. Qualitative inquiry offers powerful insights into the drivers of social and behavioural phenomena but remains under‐represented in ecological research despite its broadening demographic. This presents a substantial missed opportunity that warrants rectifying. Here, we outline the qualitative research paradigm and highlight its benefits to ecology and ecologists. We also discuss a range of pitfalls and caveats ecologists encounter by not using appropriate qualitative research designs to support the exploration of their questions. We conclude by providing guidance for ecologists who intend to conduct research embracing qualitative or mixed paradigm designs. In order to address the human dimensions of ecology and conservation, it is essential to engage qualitative experts within and beyond the ecological science community. When fruitful collaborations form, research teams are able to approach some of ecology's most challenging problems from new perspectives, incorporating the views and knowledge of stakeholders on whom we rely for success.